Ku świadomemu i kompetentnemu ojcostwu – analiza serwisów parentingowych - Dankowska-Kosman , Małgorzata (Studia Edukacyjne, 2021)
As part of this study, an analysis of dynamically developing parenting websites was undertaken. Particular attention was paid to their popularity amongst men. This is both about the receipt of information and the possible participation in discussions or comments on ventures. Research topić has taken the form of a question: What information and where do modern fathers look for? The empirical material was juxtaposed with the findings included in the subject literature.